Periosteal Turnover Flap for Coverage and Salvage of Exposed Deep Brain Stimulation Device - Baghaki S.; Yalcin C. E.; Mazlum L. C. (My University, 2023)
Implanted deep brain stimulation (DBS) devices are crucial in the treatment of movement disorders. Hardware extrusion is among the most frequent complications of the implantation process and requires reconstruction with well-vascularized tissues. The authors present a case of periosteal turnover flap for coverage of an exposed DBS device. An 11-year-old female patient with spastic cerebral palsy presented with an exposed DBS device located in the right parietal area. The exposed device was covered by a proximally based periosteal flap. Postoperative evaluations at months 1, 2, 3, and 8 revealed no signs of infection or dehiscence. This brief clinical study shows that reconstruction with periosteal turnover flaps is both an easy and excellent choice for secondary closure of exposed DBS devices.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Health Sciences; Cerrahi; Klinik Tıp; Klinik Tıp (Med); Surgery; Clinical Medicine; Clinical Medicine (Med)